KERUDUNG SANTET GANDRUNG : SIMBOL PERLAWANAN TERHADAP KAUM SANTRI BANYUWANGI - Sungkowati, Yulitin (Diksi, 2015)
A literary work as a cultural artifact is a verbal symbol that has to be interpreted in a broad context because it correlates with the writer’s intention in responding to an experienced situation. Kerudung Santet Gandrung is a novel set in Banyuwangi representing the life of practitioners of the Gandrung traditional art and that of santris, people studying at Islamic religious boarding schools. There are many symbols in the novel which potentially could be seen as indications of textual elements in the dynamic relation between the two different communities. By using a cultural hermeneutic approach, the novel strives to depict an effort in resistance made by Hasnan Singodimayan, an observer of Banyuwangi culture, to reconstruct a new and positive image of traditional artists. His resistance is an attempt to preserve Banyuwangi traditional arts which are threatened with extinction by Islamic purification movements. Keywords: novel, Gandrung, symbol, resistance